Research on the Computational Prediction of Essential Genes - Guo, Yuxin; Ju, Ying; Chen, Dong; Wang, Lihong (Frontiers in Cell and Developmental Biology, 2021)
Genes, the nucleotide sequences that encode a polypeptide chain or functional RNA, are the basic genetic unit controlling biological traits. They are the guarantee of the basic structures and functions in organisms, and they store information related to biological factors and processes such as blood type, gestation, growth, and apoptosis. The environment and genetics jointly affect important physiological processes such as reproduction, cell division, and protein synthesis. Genes are related to a wide range of phenomena including growth, decline, illness, aging, and death. There is a class of genes that have been highly conserved in multiple organisms during evolution. They are generally located on the dominant strand of DNA and can be expressed at very high levels. The proteins they encode usually have very important functions or are responsible for maintaining and repairing components of essential functions. Such genes are therefore known as persistent genes. Genes that are indispensable for biological activities are essential genes. For example, when starch is the only source of energy, the genes related to starch digestion are essential genes. Without them, the organism will die because it cannot obtain enough energy to maintain basic functions. The proteins encoded by essential genes are indispensable for the organism’s survival. Nowadays, DNA can be extracted from blood, saliva, or tissue cells for genetic testing, and detailed genetic information can be obtained using the most advanced scientific instruments and technologies. The information gained from genetic testing is useful to assess the potential risks of disease, and to help determine the prognosis and development of diseases. Such information is also useful for developing personalized medication and providing targeted health guidance to improve the quality of life. Therefore, it is of great theoretical and practical significance to identify important and essential genes. In this paper, we outline the current status of genetic research and bacterial genome databases, and summarize recent research on the computational prediction of essential genes. We introduce some of the new methods to identify genes based on the theory of communication coding. Finally, we discuss the significance of identifying essential genes for research and practical purposes.